Propionic and Methylmalonic Acidemias: Initial Clinical and Biochemical Presentation - Amira Mobarak; Heba Dawoud; Wesam A. Mokhtar; Abdelrahim A. Sadek; Gihan Mohamed Bebars; Amr Ahmed Othman; Rofaida M. Magdy; Hanaa Nofal; Amr Zoair (Hindawi Limited, 2020)
PA and MAA have numerous nonspecific presentations, potentially leading to delayed diagnosis or misdiagnosis. In this paper, we present the clinical and biochemical characteristics of MMA and PA patients at initial presentation. Results. This is a retrospective review of 20 patients with PA (n=10) and MMA (n=10). The most observed symptoms were vomiting (85%) and refusing feeding (70%). Ammonia was 108.75±9.3 μmol/l, showing a negative correlation with pH and bicarbonate and positive correlation with lactate and anion gap. Peak ammonia did not correlate with age of onset (r=0.11 and p=0.64) or age at diagnosis (r=0.39 and p=0.089), nor did pH (r=0.01, p=0.96; r=−0.25, p=0.28) or bicarbonate (r=0.07, p=0.76; r=−0.22, p=0.34). There was no correlation between ammonia and C3 : C2 (r=0.1 and p=0.96) or C3 (r=0.23 and p=0.32). The glycine was 386±167.1 μmol/l, and it was higher in PA (p=0.003). There was a positive correlation between glycine and both pH (r=0.56 and p=0.01) and HCO3 (r=0.49 and p=0.026). There was no correlation between glycine and ammonia (r=−0.435 and p=0.055) or lactate (r=0.32 and p=0.160). Conclusion. Clinical presentation of PA and MMA is nonspecific, though vomiting and refusing feeding are potential markers of decompensation. Blood gas, lactate, and ammonia levels are also good predictors of decompensation, though increasing levels of glycine may not indicate metabolic instability.